Flood Vulnerability Assessment of an Urban Area: A Case Study in Seoul, South Korea - Lee, Seonmi; Choi, Youngje; Ji, Jungwon; Lee, Eunkyung; Yi, Sooyeon; Yi, Jaeeung (Water (Switzerland), 2023)
Climate change has led to frequent and extreme flooding events in urban areas such as Seoul, a city that is particularly vulnerable due to drainage systems that were not originally designed to handle such conditions. This study aims to develop region-specific storm risk matrices for the 25 districts in Seoul and predict storm risks. By accounting for local meteorological and geographic characteristics, these matrices will enable a more targeted approach to issuing heavy rainfall warnings, as opposed to the current nationwide system. The methodology involves calculating entropy weight based on various factors, assessing flood vulnerability, and estimating region-specific rainfall associated with warning levels. These warning levels are then used to create storm risk matrices, which are tested for conformity against historical flood events. Finally, a storm risk prediction technique is developed using rainfall forecasting data. Results demonstrate the feasibility of using the newly developed storm risk matrices to predict flood damage up to 72 h in advance. This greatly contributes to the development of effective mitigation plans for addressing climate change-driven urban flood damage. The study’s findings offer valuable insights for enhancing local-specific heavy rainfall warning systems and ensuring better preparation in the face of increasing urban flood risks due to climate change.
Keywords: Case-studies; Ensemble prediction systems; Flood vulnerabilities; Heavy rainfall; Local ensemble prediction system; Risk matrix; South Korea; Storm risk matrix; Urban areas; Vulnerability assessments; climate change; flood vulnerability; local ensemble prediction system; storm risk matrix